PENINGKATAN KETRAMPILAN PRAKTEK SISWA PADA PEKERJAAN SAMBUNGAN KONSTRUKSI KAYU MELALUI METODE TUTORIAL INDIVIDUAL SILANG - Sukardi, Sukardi (Universitas Muhammadiyah Magelang, 2009)
Issues raised today that the gap between school and real life in the community What are learned in school is another thing that happens in society, which pointed out the school further away with the learners' work. Therefore, students need to given life skills (life skills), then the practical skills students need to be improved, an effort to improve students' practical skills tutorial the author uses the method of individual cross-examination, turn out quite well